Oral monitoring of a pediatric patient during chemotherapy treatment - Isabella Lima Arrais Ribeiro; Ana Maria Gondim Valença; Paulo Rogério Ferreti Bonan; Fabíola Galbiatti de Carvalho Carlo
Oral side effects must be expected during cancer treatment on pediatric patients. Monitoring side effects on oral cavity of antineoplastic therapy is desirable but sometimes performed without criteria. The purpose of this article is to describe an oral monitoring in an male with Hodgkin lymphoma during chemotherapy treatment using an Oral Assessment Guide. An 11-yr-old male was assisted during all treatment of chemotherapy against Hodgkin's lymphoma in the dental sector of a hospital of reference of João Pessoa, Paraíba, Brazil. The Oral Assessment Guide was applied by a calibrate examiner and was observed the emergence of ulcerative lesions on the labial mucosa emerged on two different periods (D15- primary cycle; D15-second cycle) and the major values of oral mucositis were verified in D1 e D15 periods of second cycle of chemotherapy. Monitoring oral side effects during antineoplastic therapy could prevent severe oral complications and avoid to associate systemic complications.